Am I my IP address's keeper? Revisiting the boundaries of information privacy. Issue 3 (27th May 2017) - Hildén, Jockum
ABSTRACT: Whether the Internet Protocol address should be seen as personal data or not remains a contested issue with regard to information privacy. This article explores the question by looking at the technical attributes of the Internet Protocol address, European Union (EU) and U.S. case law, and how the EU's advisory data protection body, the Article 29 Working Party, and some of the world's most influential information and communication technology (ICT) companies consider the IP address. The notion of contextual integrity is then used to show that information privacy regulation must stipulate concrete technical mandates instead of guiding principles, contrary to the ideal of technology neutrality in Internet regulation.